INPUT/OUTPUT PROCESSOR IP CORE- ASHl - HASHIM, ABDULLAH SHAMIL (Universiti Teknologi PETRONAS, 2011)
Any computer system has an input/output (I/O) subsystem that enables it to communicate with the outside world via I/O devices (peripherals). The input/output subsystem provides the point ofaccess for a user to enter or get data through peripherals that can be used in various aspects of daily-life applications. However, peripherals are different intheir characteristics in terms of speed (among each otherand with respect to the computer system) and communication protocols which makes it necessary to have such specialized communication links as isolated (dedicated) I/O bus or memorymapped I/O bus between the central processing unit (CPU) and these peripherals. Since the early history of computers, people have tried to resolve peripheral differences through such methods as polling, interrupts, direct memory access and I/O processors. This project aims to build an I/O processor to communicate with peripherals relieving the CPU from I/O tasks and enabling it to perform other tasks in parallel. The project is done for its sponsor Aeste Works (M) Sdn Bhd. It is involved with conducting an extensive study on I/O operations to design a processor that is dedicated to such operations. Within a period of twenty six weeks, the processor was designed and verified. It isnow able to perform the I/O tasks ofboth Universal Serial Bus (USB) and Ethernet. This document is a thesis which presents in details an introduction about the project along with its literature review, methodology, results and discussion. Itends with a conclusion andhighlighting some recommendations.